Perancangan Aplikasi M-Learning Untuk Pembelajaran Ebusiness Bagi Mahasiswa Dengan Menggunakan Perangkat Mobile Berbasis Android - Andrianof, Harkamsyah (Prodi Sistem Informasi Universitas Dharma Andalas, 2020)
In supporting the success and smoothness the process of learning, the thing that must be considered is learning resources. With the fast development of technology at the moment, the learning resources are not limited to conventional media such as text books. The content that comes from books currently has been transformed into digital form with more effective and efficient learning models, such as Mobile learning. In this case, the author is motivated to develop a software that functions as a learning medium by utilizing the benefits of a mobile smartphone based on the Android operating system. This software can be a learning media that make it easy to learn e-business science with priority material about e-business infrastructure. This application has the aim to assist teachers in delivering material outside of lecture hours, making it easier for students to learn through smartphones that can increase student interest in learning.